Academics during the 90ies - A study of working conditions for members of the Swedish Confederation of Professional Associations (SACO) - Härenstam, Annika; Aronsson, Gunnar; Bejerot, Eva (Arbetslivsinstitutet, 2018)
The purpose of the survey was to obtain current knowledge about the work situation, as well as deepened understanding for important conditions, for different occupational groups with academic background. A questionnaire was sent to every fiftieth member of the Swedish Confederation of Professional Association (SACO).
The questionnaire was divided into following areas: background, in-service training, work organisation, health, work and family.

Syftet med undersökningen var att få fram tidsaktuell kunskap om arbetssituationen i akademikeryrken och en fördjupad insikt i väsentliga förhållanden för olika yrkesgrupper. En enkät skickades ut till var 50:e SACO-medlem.
Enkäten var indelad i följande frågeområden: Bakgrundsfrågor, kompetensutveckling, arbetsorganisation, hälsa samt arbete och familj.
Akademiker under 90-talet - En studie av SACO-medlemmars arbetsvillkor - Akademiker under 90-talet. En studie av SACO-medlemmars arbetsvillkor
Keywords: health; hälsa; leisure time; fritid; job satisfaction; arbetstillfredsställelse; domestic responsibilities; hushållsansvar; unemployment; arbetslöshet; family life; familjeliv; trade union membership; medlemskap i fackförening; educational background; utbildningsbakgrund; autonomy at work; autonomi i arbetet; work attitude; inställning till arbete; workplace; arbetsplats; lifelong education; livslångt lärande; research; forskning; globalization; globalisering; personnel management; personalledning; workloads; arbetsbörda; sick leave; sjukfrånvaro; part-time employment; deltidsarbete; working conditions; arbetsförhållanden; computers; datorer; General health and well-being; Allmän hälsa och välbefinnande; Employee training; Vidareutbildning inom arbetet; Working conditions; Arbetsförhållanden; Gender and gender roles; Kön och könsroller; Family life and marriage; Familjeliv och äktenskap; Social Sciences; Samhällsvetenskap; Sociology; Sociologi; Work Sciences; Arbetslivsstudier